Investigation of patient and observer agreement on description of seizures at initial clinical visit. Issue 12 (5th December 2019) - Saleem, Maha N.; Arencibia, Christopher A.; McKenna, Kevin; Cristofaro, Sabrina; Detyniecki, Kamil; Friedman, Daniel; French, Jacqueline; Blumenfeld, Hal
Abstract: There have been few studies of agreement between seizure descriptions obtained from patients and observers. We investigated 220 patients and observers who completed structured questionnaires about patients' semiological seizure features at the initial clinical visit. Inter‐rater reliability was assessed using Cohen's kappa and indices of positive and negative agreement. Patients and observers had excellent agreement on the presence of memory impairment and generalized shaking and stiffness during seizures. In addition, patients under‐reported seizure descriptions more easily observed externally, whereas observers under‐reported change in patient location at seizure end. These findings may guide interpretation of clinical histories obtain in epilepsy care.